KARAKTERISRIK SENSORIS DAN FISIKO KIMIA SELAI CAMPURAN BUAH SIRSAK (Annona muricata L) DENGAN UBI JALAR UNGU (Ipomea batatas L) - Hendra Rahim; Teltje Koapaha; Jan R. Assa (COCOS, 2022)
ABSTRACT This study aims to obtain the ratio of soursop fruit and purple sweet potato favored by the panelists and to analyze the chemical composition of the resulting jam. The chemical compositions tested were water content and total dissolved solids. This study used a completely randomized design (CRD) with 5 treatments with variations of soursop fruit pulp and purple sweet potato pulp, each treatment was repeated three times. The results showed that the ratio of soursop fruit and purple sweet potato had a significant effect on the water content but had no significant effect on the total soluble solids of the resulting jam. The composition of the resulting water content ranged from 38.56% - 46.58% and the total dissolved solids ranged from 65.66 brix – 66.66 brix. Based on the results of the sensory analysis of the panelists' preference for purple sweet potato soursop jam, namely color 3.76 - 6.08 (neutral - like), aroma 3.60 - 4.24 (neutral), taste 4.28 - 5.40 ( neutral - somewhat like), and texture 4.84 - 5.56 (somewhat like - like). Spreading power 5.36 -6.08 jam (easy to spread). And the jam color (color grab) L (brightness) 39.90 – 69.73. a* (reddish red) 3.80 – 42.23. And b* (red-brown) 8.89 – 19.36. Keywords: Jam, Soursop, Purple Sweet Potato